Effect of light‐level geolocators on apparent survival of two highly aerial swift species. (24th October 2017) - Morganti, Michelangelo; Rubolini, Diego; Åkesson, Susanne; Bermejo, Ana; de la Puente, Javier; Lardelli, Roberto; Liechti, Felix; Boano, Giovanni; Tomassetto, Erika; Ferri, Mauro; Caffi, Mario; Saino, Nicola; et al.
Abstract : Light‐level geolocators are currently widely used to track the migration of small‐sized birds, but their potentially detrimental effects on survival of highly aerial species have been poorly investigated so far. We recorded capture–recapture histories of 283 common swifts Apus apus and 107 pallid swifts Apus pallidus breeding in 14 colonies in Italy, Spain, Sweden and Switzerland that were equipped with 10 different types of geolocators ('geolocator birds'), and compared their survival with that of, respectively, 215 common and 101 pallid swifts not equipped with geolocators ('control birds'). Data were analysed using both GLMMs with return rate as a proxy for survival and mark–recapture models to estimate survival while accounting for recapture probability. In all the analyses, geolocator birds showed reduced apparent survival compared to controls. Geolocator weight was always lower than 3% of body mass, and did not affect survival per se. Geolocators with a light‐stalk, which is used in some geolocator models to reduce light sensor shading by feathers, decreased apparent survival more than models without light‐stalk. Apparent survival of geolocator birds significantly varied among sites, being much higher in northern Europe. Despite in our analyses we could only partly account for variable recapture probabilities among sites and for inter‐annual variability in survival, our results generally showed that equipping swifts with geolocators decreased their survival prospects, but also that the magnitude of this effect may depend on species‐specific traits. These conclusions are in line with those of other studies on aerial foragers. We suggest that future studies tracking the movements of aerial insectivorous birds should use devices designed to minimize drag.